Animal health in subhumid Nigeria - Maina, J.A. (International Livestock Centre for Africa, 1986)
Presents results of animal health studied in cooperating pastoralists' herds in the subhumid zone of Nigeria comparing incidence of rinderpest, foot and mouth disease, contagious bovine pleuropneumonia, dermatophilosis, lumpy skin disease, brucellosis papillomatosis and Keratoconjunctivitis & helminthiasis and degree of tick infestation in them and herds within Kachia Local Government area. Reports weight gain responses of Bunaji calves following anthelmintic treatment.